Unemployment and work disability in individuals with chronic fatigue syndrome/myalgic encephalomyelitis: a community-based cross-sectional study from Spain - Jesús Castro-Marrero; Mónica Faro; María Cleofé Zaragozá; Luisa Aliste; Tomás Fernández de Sevilla; José Alegre (BMC Public Health, 2019)
Abstract Background Few reports have examined the association between unemployment and work disability in Chronic Fatigue Syndrome/Myalgic Encephalomyelitis (CFS/ME). This study explored the key determinants of work disability in a CFS/ME cohort. Methods A community-based prospective study included 1086 CFS/ME patients aged 18–65 years. Demographic and clinical characteristics and outcome measures were recorded. Multiple linear regression analysis was performed to identify key risk indicators of work disability. Results Four hundred and fifty patients with CFS/ME were employed (41.4%) and 636 were unemployed (58.6%). Older age at pain onset (OR: 1.44; 95% CI: 1. 12–1.84, autonomic dysfunction (OR: 2.21; 95% CI: 1.71–2.87), neurological symptom (OR: 1.66; 95% CI: 1. 30–2.13) and higher scores for fatigue (OR: 2.61; 95% CI: 2.01–3.39), pain (OR: 2.09; 95% CI: 1.47–2.97), depression (OR: 1.98; 95% CI: 1. 20–3.26), psychopathology (OR: 1.98; 95% CI: 1.51–2.61) and sleep dysfunction (OR: 1.47; 95% CI: 1. 14–1.90) were all associated with a higher risk of work disability due to illness. Conclusions Using an explanatory approach, our findings suggest that unemployment is consistently associated with an increased risk of work disability due to CFS/ME, although further more rigorous research is now needed to help in targeting interventions at the workplace.